The Net and the newsroom an exploratory study on how journalists from the Philippine Daily Inquirer and GMA Network Inc. use the internet for information-gathering and information-dissemination - de los Reyes, Jonas Renojo 1977-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The explosion of the Internet has hit almost every aspect of society. From education to politics, art to mass media, the Internet has made its way into our lives just like that. The field of journalism is especially affected as journalistic media experience changes not just in the gathering of information but also in its dissemination as well. This leads to the question, how are Filipino journalists utilizing the Internet as a medium of information-gathering and information-dissemination? This exploratory study attempted to answer that question through in-depth interviews with journalists from the Philippine Daily Inquirer and GMA Network Inc. and through a qualitative content analysis of their respective websites or online newspapers. The study revealed that these journalists have so far just been using two Internet software applications for information-gathering. Yet this has had positive effects on them as there is now efficient access to a wide range of information and an easier and faster means of communication. Likewise their articles and reports were better because of story angles and perspectives and more background information and content. However this does not exempt them from any negative side effect for with the use of Internet, they are faced with the dilemma of proving the authenticity of online information, and connection and website problems. They also face the ethical problem and the possible use of unverified data on their reports. In the information-dissemination aspect, they have online newspapers that publish through the World Wide Web. These websites have employed both traditional media elements and the new media elements in the Internet though not as extensively as may be. Fonts, photographs, multimedia and color were the traditional media elements were not extensively used while all media elements of access (hyperlinks and navigational bars), depth (number of pages with related information), interactivity (e-mails, forums, forms, chats, etc.) and web trade elements (asking for subscription, advertisements) were failed to be applied to their fullest potential.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Online journalism -- Philippines; Philippine Daily Inquirer -- Philippines -- Internet research; GMA Network Inc. -- Philippines -- Internet research